BARRIERS TO CHILDREN’S PARTICIPATION IN AGENCIES ADDRESSING CHILD LABOUR IN ZAMBIA: THE CASE OF LUSAKA CITY - Michelo Chilwalo (European Scientific Journal, ESJ, 2015)
Child labour still remains one of the challenging social problems Zambia is grappling with hitherto. Despite numerous efforts that have been embarked on to address this problem, children’s participation in the fight against child labour is minimal and in some instances, is hardly recognised at all. The present study aims to explore the barriers that hinder children’s participation in agencies addressing child labour in Zambia. In-depth interviews with key informants and focus group discussions with children were conducted, which included 12 agency staff and 30 children from poor families who were engaged in child labour respectively, using semistructured checklists. Agency staff and children were purposively sampled whilst those not known during the initial sampling process were sampled using snowball during the course of the study. All interviews and focus group discussions were digitally recorded. By using thematic and content analysis to identify patterns and themes from the data, five major barriers were identified: culture, adults’ negative attitudes towards children, poverty, lack of information among children, and generally participation being perceived as a waste of time. Results show that the idea and value of children participation in decision making is not only misunderstood but also unaccepted amongst practitioners in agencies addressing child labour. However, these barriers can be addressed if children are perceived as stakeholders in decision making and by addressing poverty at household level. The author proposes the integration of the human rights-based approach in agency programming to inform practitioners, as it incorporates the principles of participation, accountability, non-discrimination and empowerment.